'Cyber warfare' in style: Cambridge Analytica and a mediatized ethics of fashion. (1st April 2022) - Halliday, Rebecca
On 29 November 2018, Christopher Wylie ‐ a former Ph.D. researcher in fashion trends and the whistleblower of Cambridge Analytica ‐ delivered a speech to The Business of Fashion's VOICES conference, detailing how the firm harvested the data of more than 87 million Facebook users and utilized fashion psychographic brand preferences as measurable and estimable data that could be manipulated to influence political opinion through targeted psychographic social media content. This article takes Cambridge Analytica as a point of departure to explore interstices between fashion brands and consumers, and entrenched surveillance, in a mediatized field of fashion and within the culture wars. Jodi Dean's concept of communicative capitalism, in which consumer statements take the form of affective bursts disseminated into and captured via the network under a market logic, articulates how our desires and/as identities can be honed to alter democratic processes and outcomes. Extending an affect framework, I posit that formations of consumer or user affect characterize relations between fashion companies and consumers in a politicized climate. This paper issues a call to scrutinize issues of media ethics, discourse and surveillance that these cases raise via a fashion studies perspective that perceives aesthetic preference as formative and reflective of global politics.